Impact of Gender-Neutral Retail Design: An Investigation into Spatial Inequalities Prevalent in Fast Fashion Stores - Azad, Kaavya; MR, Akshaya (MAJ - Malaysia Architectural Journal, 2025)
In the contemporary context, Generation Z challenges established norms, notably exemplified by the evolving gender spectrum. As societal attitudes toward identity continue to shift, architecture must adapt to ensure user comfort and safety. Fashion plays a crucial role in shaping personal identity, making retail spaces pivotal in reflecting and promoting these evolving values while fostering security. However, persistent gender segregation in fast fashion contributes to spatial inequalities. This paper employs qualitative methods to explore the impact of gender-neutral retail design, aiming to mitigate these disparities. The study focuses on spatial and visual elements within fast fashion stores, including circulation, spatial planning, display methods, colour, and finishes. Given its resonance with Generation Z, this demographic serves as the primary sample group. Through literature reviews, case studies, and surveys, the research seeks to understand customer perceptions of these design parameters and formulate guidelines for gender-neutral retail design. Ultimately, this endeavour aims to offer practical recommendations aligned with Generation Z preferences, fostering a more inclusive and equitable retail environment.